COMPARATIVE STUDY ON ANGIOTENSIN CONVERTING ENZYME INHIBITORY ACTIVITY OF HYDROLYSATE OF MEAT PROTEIN OF INDONESIAN LOCAL LIVESTOCKS - Jamhari, J.; Yusiati, L.M.; Suryanto, E.; Cahyanto, M.N.; Erwanto, Y.; Muguruma, M. (Diponegoro University, 2013)
The experiment was conducted to investigate the angiotensin converting enzyme (ACE) inhibitoryactivity of hydrolysate in meat protein of Bali cattle, Kacang goat, native chicken, and local duck. Themeats of Bali cattle, Kacang goat, native chicken, and local duck were used in this study. The meatswere ground using food processor added with aquadest to obtain meat extract. The meat extracts werethen hydrolyzed using protease enzymes to obtain hydrolysate of meat protein. Protein concentration ofmeat extract and hydrolysate of meat protein were determined, and were confirmed by sodium dodecylsulfate - poly acrylamide gel electrophoresis (SDS-PAGE). ACE inhibitory activity of hydrolysate ofmeat protein derived from Bali cattle, Kacang goat, native chicken, and local duck was also determined.The results showed that protein concentration of hydrolysate of meat protein of Bali cattle, Kacang goat,native chicken, and local duck meat was significantly higher than their meat extracts. SDS-PAGEanalysis indicated that hydrolysate of meat protein of Bali cattle, Kacang goat, native chicken, and localduck had more peptides with lower molecular weight, compared to their meat extracts. Hydrolysate ofmeat protein of Bali cattle, Kacang goat, native chicken, and local duck had potencies in inhibiting ACEactivity, so it will potentially reduce blood pressure.